2006
DOI: 10.1007/s11090-005-8722-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-Catalytic Decomposition of Phenols in Atmospheric Pressure Dielectric Barrier Discharge

Abstract: This study investigated the processes for the destruction of phenol and its derivatives (resorcin and pyrocatechol) in aqueous solutions under the action of an oxygen dielectric barrier discharge (DBD) at atmospheric pressure in the presence or absence of catalysts in the plasma zone. It was shown that the DBD had a high decomposition efficiency for phenol and its derivatives (up to 99%). Phenol was the most stable and pyrocatechol was the least. In a plasma-catalytic hybrid process, the effective rate constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 8 publications
1
27
0
Order By: Relevance
“…The activation of catalyst placed inside of a BaTiO 3 packed-bed plasma reactor was also observed in [11,12]. It was reported that plasma could initiate the benzene decomposition on photocatalyst (TiO 2 , Ag/TiO 2 and Pt/TiO 2 ) at as low temperature as 100°C.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The activation of catalyst placed inside of a BaTiO 3 packed-bed plasma reactor was also observed in [11,12]. It was reported that plasma could initiate the benzene decomposition on photocatalyst (TiO 2 , Ag/TiO 2 and Pt/TiO 2 ) at as low temperature as 100°C.…”
Section: Discussionmentioning
confidence: 95%
“…Hence, in order to improve and increase the efficiency of VOC decomposition, an innovative technology has been proposed where a V. Demidyuk AE J. C. Whitehead (&) School of Chemistry, The University of Manchester, Oxford Road, Manchester M13 9PL, UK e-mail: christopher.whitehead@manchester.ac.uk plasma reactor was coupled with a catalytic reactor [8][9][10][11][12][13]. Such a combination helps overcome some of the disadvantages of both catalytic and plasma treatments.…”
Section: Introductionmentioning
confidence: 99%
“…There are several discharge types and discharge setups for close contact obtained between plasma and a solution. These include glow discharges with one or two liquid electrodes [1][2][3], pulse positive streamer corona discharges generated in aqueous solutions [4][5][6] and dielectric barrier discharges (DBD) [7]. The application of a catalyst is another way of enhancing the process.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the application of heterogeneous catalysts is more preferable. It was previously reported [7] that catalysts based on CuO and NiO increased the decomposition efficiency of phenol, resorcin and pyrocatechol in aqueous solutions through the action of an atmospheric pressure DBD in oxygen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation